The Role of Technology in Improving the Effectiveness of Employee Training at PT Wijaya Kusumo Joyo Mulyo - Muhammad Maulana Ardiansyah; Mochammad Isa Anshori (Journal of Transformational Human Resource Management, 2025)
Outsourcing companies face challenges in ensuring the competence and quality of the workforce provided to clients. Employee training and development are essential strategies to maintain service quality and increase company competitiveness. This study aims to analyze the role of technology in enhancing the effectiveness of training and employee development at PT Wijaya Kusumo Joyo Mulyo, an outsourcing service provider. This research employs a qualitative approach with data collection techniques including interviews, observation, and documentation. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. The results indicate that the use of technology, such as Learning Management Systems (LMS), e-learning platforms, and online communication tools, significantly improves the effectiveness of training for outsourced employees. Technology provides broader accessibility, cost and time efficiency, and enables data-driven monitoring. Furthermore, the integration of technology supports the standardization of competencies across employees assigned to various client locations. Challenges include limited digital literacy among some employees and the need for adequate technological infrastructure. The implications of this research highlight the importance of implementing technology-based training strategies aligned with client requirements, strengthening employees' digital literacy, and ensuring continuous evaluation to optimize the benefits of technology.